Anti-mold, self-cleaning superhydrophobic bamboo fiber/polypropylene composites with mechanical durability - Zhao, He; Lin, Xinxing; Lu, Shengchang; Wu, Hui; Zhou, Xiaxing; Huang, Liulian; Li, Jianguo; Shi, Jianping; Tong, Wenxuan; Yuan, Hongmei; Chen, Lihui (Frontiers in Chemistry, 2023)
Bamboo fiber/polypropylene composites (BPC) have been widely used in building, interior decoration, and automobile components. However, pollutant and fungus can interact with the hydrophilic bamboo fiber on the surface of BPC, decreasing the appearance and mechanical properties of BPC. To improve the anti-fouling and anti-mildew properties, a superhydrophobic modified BPC (BPC-TiO2-F) was fabricated by introducing titanium dioxide (TiO2) and poly(DOPAm-co-PFOEA) copolymer into the surface of BPC. The morphology of BPC-TiO2-F was analyzed by XPS, FTIR, and SEM. The resulted showed that TiO2 particles was successfully covered on BPC surface through the complexation between phenolic hydroxyl group and Ti. The fluorine-containing poly(DOPAm-co-PFOEA) with low surface energy was introduced into BPC surface, forming rough micro/nano structure on the surface of BPC to endow BPC-TiO2-F superhydrophobic properties with contact angle of 151.0±0.5°. The modified BPC exhibited excellent self-cleaning property, and the contaminant of Fe3O4 powder were taken away from the surface of modified BPC rapidly by water drop. The BPC-TiO2-F showed excellent anti-mold performance and no mold left on the surface of BPC-TiO2-F after 28 days. The superhydrophobic BPC-TiO2-F have good mechanical durability to withstand sandpaper abrasion with a weight load of 50 g for 20 cycles and tape adhesion abrasion for 50 cycles. The BPC-TiO2-F with good self-cleaning, mildew resistance and mechanical resistance has promising application in automotive upholstery and building decoration.